Pengaruh Kepuasan Kerja, Motivasi Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai: Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas II Jayapura - Arthur, Eddy; Syauta, Jack H.; Wanma, Johanis R. (Magister Manajemen Universitas Cenderawasih, 2024)
This study aims to analyze the influence of job satisfaction, work motivation, work discipline, and work environment on the performance of employees at the Office of Class II Port Authority and Harbormaster Jayapura, both simultaneously and partially. The study also seeks to identify the variable that has the most dominant influence on employee performance. The sample in this study consisted of 66 employees, and the data analysis technique used was multiple regression, processed using SPSS version 23. The results indicate that the variables of job satisfaction, work motivation, work discipline, and work environment simultaneously have a positive and significant effect on employee performance. Partially, the variables of job satisfaction, work motivation, work discipline, and work environment also have a positive and significant effect on employee performance. Among these variables, job satisfaction is identified as the most dominant variable contributing to employee performance.